El impacto de la crisis en el uso y aprovechamiento de las TIC en las televisiones regionales públicas en España, Francia, Italia y Reino Unido - Berumen, Sergio A.; Arriaza Ibarra, Karen (Papeles de Europa, 2013)
This article is based on a research that evaluates the way in which regional public televisions in Spain, France, Italy and the United Kingdom have generated, adopted, and used ICT technology between 2007 and 2012 – years in which a landscape of economic crisis has changed the European economy. With the aim of carrying out a differential evaluation with the selected indicators, a model indicator was constructed. The general conclusion that came from the empirical work indicated that in the case of regional public broadcasters in the United Kingdom and in France the economic crisis has not had very harmful effects, while in the cases of Italy and Spain the devastating effects on the public service regional broadcasters have been evident.